The development potential of the community in Participant Model to Sustainable Tourism Community - Chomphoopanya, Anuwat; Rojanatrakul, Tanastha (Journal of Modern Learning Development, 2022)
Strength economic foundations is the economic system of the local community that can be self-reliant and mutual help. It is an economic system that develops in various areas in the dimension of society, people, communities, cultures, environments, and natural resources to be strong and sustain, create a career and distribution of income, reduce the problem of inequality at the community level. In addition, the fundamental economy must have its own development and management approach by the local community until it can be developed into a community enterprise or a community business. Tourism is another option to develop strength economic foundations. Because nowadays tourism has many forms. Tourism that is connected to the community and sustainable is community tourism. Factors contributing to successful community-based tourism can develop a strong community-based economy that requires community participation, conservation, and the relationship between people in the community and natural resources in the form of tourism and community development. to strengthen local communities through the process of developing capacity with participation of people in the community. The community can use the potential of resources such as people, natural resources, culture, customs and traditions to develop efficiency for community tourism. In this regard, in the development of community capacity with participation, it can lead to sustainable community tourism and generate income for people in the community. They can also develop communities that are outstanding in various fields to become a tourism community that can generate income in the community leading to a strong and sustainable economy.